Mathematical Modeling and Analysis of Immobilized Glucose Dehydrogenase Reactions in Spherical Micro-reactors (European Journal of Pure and Applied Mathematics, 2025)
In this article, a batch stirred tank reactor comprising an array of uniform spherical porous micro-reactor (MR) immobilized with nonspecific glucose dehydrogenase and an oxygen-reducing enzyme is modeled mathematically. This model is a steady-state system of non-linear reaction diffusion terms related to the non-Michaelis-Menten kinetics of an enzymatic reaction. We provide approximate analytical expression of the non-linear reaction diffusion equations of substrate, product and oxygen concentrations by utilizing the Adomian Decomposition Method (ADM) and Taylor Series Method (TSM). The obtained semi-analytical results are compared with the numerical simulations, satisfactory results are obtained. Semi-analytical expression for the effectiveness factor of the system is also provided. Using this expression, the factors influencing the effective operation of the system are discussed.